2016
DOI: 10.1016/j.matdes.2016.06.121
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cu 6 Sn 5 in TiO 2 reinforced solder joints after multiple reflow cycles

Abstract: In the current generation of 3D electronic packaging, multiple reflows are often required during soldering. In addition, electronic packages may be subjected to additional solder rework or other heating processes. This paper investigates the effects of multiple reflow cycles on TiO2 reinforced Sn-0.7Cu solder fabricated by a powder metallurgy microwave sintering technique.Compared to TiO2-free equivalents, a relative suppression of the Cu6Sn5 phase, both as primary crystals and as an interfacial layer was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…As in Figure 2a However, the interfacial Cu3Sn layer of the reinforced Sn0.7Cu was slightly thicker compared to the non-reinforced Sn0.7Cu. As reported by Mohd Salleh et al (2016b), the grooves between the Cu6Sn5 scallops play a critical role in the growth of Cu-Sn interfacial layer and during annealing, the grooves serves as diffusion paths of Cu into the solder. It is also reported that during soldering, the TiO2 particles come into intimate contact with the Cu6Sn5 interfacial layer modifying the Cu diffusion and dissolution path into the molten solder and preventing individual Cu6Sn5 grains from growing further and reducing the Cu6Sn5 channels.…”
Section: Microstructure Of Annealed Solder Jointsmentioning
confidence: 75%
“…As in Figure 2a However, the interfacial Cu3Sn layer of the reinforced Sn0.7Cu was slightly thicker compared to the non-reinforced Sn0.7Cu. As reported by Mohd Salleh et al (2016b), the grooves between the Cu6Sn5 scallops play a critical role in the growth of Cu-Sn interfacial layer and during annealing, the grooves serves as diffusion paths of Cu into the solder. It is also reported that during soldering, the TiO2 particles come into intimate contact with the Cu6Sn5 interfacial layer modifying the Cu diffusion and dissolution path into the molten solder and preventing individual Cu6Sn5 grains from growing further and reducing the Cu6Sn5 channels.…”
Section: Microstructure Of Annealed Solder Jointsmentioning
confidence: 75%
“…X-ray imaging using synchrotron radiation has allowed observation of the solidification behavior in various metallic alloys such as Sn alloys, [7][8][9][10][11][12][13][14][15][16] Al alloys, 9,10,17,18) cast iron, [19][20][21][22][23] Fe-C steels, 11,[24][25][26][27][28] and stainless steels. 29) Installing a deformation device in the observation apparatus, in-situ observation of semisolid deformation by X-ray transmission imaging (referred to as 2D observation hereinafter) was achieved with a high spatial resolution with respect to grain size.…”
Section: Introductionmentioning
confidence: 99%
“…[50] demonstrated that the doping of TiO 2 could have resulted in the refinement of microstructure of Sn-0.7wt%Cu-0.05 wt%Ni solder by the fabricate process of microwave sintered and the homogeneous (Cu, Ni) 6 Sn 5 intermetallics appear in the grains of particles. Moreover, they also investigated the evolution of Cu 6 Sn 5 IMC of TiO 2 additive Sn-0.7Cu composite solder after different reflow cycles [110]. It was confirmed that the incorporation of TiO 2 nanometer particles could suppress the growth of Cu 6 Sn 5 , which was associated with the inhibiting effect as shown in Figures 26 and 27, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 76%